Communication and Motivation Coming Out Gay as Self Identity in Indonesia - Novi Andayani Praptiningsih; Wini Tarmini; Rahmiwati Marsinun (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2020)
Many gays in Indonesia dare to admit and open themselves that they are gay. Gay who has come out (coming out) usually realizes that he likes the same sex or often called SSA (Same Sex Attraction). The term coming out refers to how a gay person opens himself up to his sexual orientation. Gay openness about his sexual orientation (coming out) to the family, community, and community is preceded by the process of coming in, namely the process of self-acceptance that he has a sexual orientation that likes same-sex. or community only. If he fails to come in, then he will become an SSA (Same Sex Attraction) but tries to suppress his behavior so he does not become gay. The purpose of this study is to determine the motivations that cause gays to become gay coming out as self-identity in Indonesia. The research method uses a qualitative approach. Data collection techniques include in-depth interviews, observation, FGD, and literature study. Data analysis uses the Miles Huberman Interactive Model. The results showed that there are 15 reasons for a person to become gay in 3 (three) contexts of the formation of gay self-identity in this study, namely family, psychological trauma, and social environment.